Method for synthesizing hetero-aggregated irregularly shaped inorganic fillers and radically polymerizable hardened products containing the same for medical and dental use
The synthesis of hetero-aggregated inorganic filler particles addresses mechanical and durability issues in dental materials by enhancing affinity and stability, resulting in high-strength, flexible dental compositions.
Patent Information
- Application Number
- JP2020072564
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-27
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2040-03-27
Smart Images

Figure 0007626985000001 
Figure 0007626985000002 
Figure 0007626985000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for synthesizing hetero-coagulated irregularly shaped inorganic fillers and to radically polymerizable cured products for medical and dental use containing the same. [Background technology]
[0002] In the medical and dental fields, metal prostheses and synthetic resin moldings are used to repair defects in bones and teeth. Adhesives containing adhesive polymerizable monomers are often used to attach them to biological hard tissues. Similarly, in the dental field, a hardenable composition called a composite resin is used clinically on a daily basis. This is done by filling an unhardened (before radical polymerization) paste into a defective part of a tooth or the like, and then applying external energy such as light irradiation to obtain a radically polymerized hardened product.
[0003] Generally, these adhesives and composite resins use (meth)acrylic acid derivative monomers such as methyl methacrylate, triethylene glycol dimethacrylate, and urethane dimethacrylate. In the free radical polymerization (hereinafter referred to as radical polymerization) of vinyl monomers such as these (meth)acrylic acid derivative monomers, the carbon-carbon double bonds are cleaved to single bonds to form a polymeric body and harden. In addition to vinyl monomers, inorganic fillers are added to the composite resin for the purpose of improving mechanical strength. In general, the inorganic fillers are surface-treated with a silane coupling agent having a polymerizable group to improve wettability and mechanical strength. In the dental field, γ-methacryloxypropyltrimethoxysilane (hereinafter referred to as KBM-503) has been widely used as a silane coupling agent. When particles surface-treated with this compound are used, there is a problem that hydrolysis easily proceeds due to low hydrophobicity, and the durability of the material is low. In addition, due to the low hydrophobicity, the filling rate of the inorganic filler is low and sufficient mechanical strength cannot be obtained.
[0004] Therefore, in order to improve the durability and filling rate of the material, a method of using a silane coupling agent with a long alkyl chain (Patent Documents 1, 2, 3), a method of using a silane coupling agent having a fluoroalkylene group (Patent Document 4), and a method of using a silane coupling agent having many polymerizable groups (Patent Document 5) have been proposed. Furthermore, a method of manufacturing an inorganic filler in which the shape of the inorganic filler is not a typical spherical or crushed shape, but is composited in anticipation of physical cohesive forces (Patent Documents 6 and 7) has also been proposed. However, in all of these methods, the melting point of the mother particle must be lower than the melting point of the daughter particle, which is inferior in versatility and industrial use. In other words, the production of the composite inorganic filler requires complicated re-grinding after synthesis. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2-134307 [Patent Document 2] Japanese Patent Application Publication No. 3-70778 [Patent Document 3] Patent Publication No. 2015-196682 [Patent Document 4] Patent Publication No. 2007-238567 [Patent Document 5] Patent Publication No. 2010-229054 [Patent Document 6] Patent No. 6452677 [Patent Document 7] Japanese Patent Publication No. 7-173410 Summary of the Invention [Problem to be solved by the invention]
[0006] When the methods described in Patent Documents 1 to 4 are applied to dental restorative materials, there is room for improvement in mechanical strength. Moreover, when the method described in Patent Document 5 is applied to dental materials, water resistance is low and durability of the materials is insufficient. In addition, methods for producing composite inorganic fillers (Patent Documents 6 and 7) have been proposed in which the shape of the inorganic filler is not generally spherical or crushed, but is composited in the hope of physical cohesive force. However, in these methods, the melting point of the mother particle must be lower than that of the daughter particle, which is inferior in versatility and industrial use. In other words, re-pulverization after synthesis is essential for the production of the composite inorganic filler. Thus, the compatibility of durability and mechanical strength of materials using silane coupling agents in the conventional technology was insufficient, and there was room for further improvement. Furthermore, the conventional methods for producing composite inorganic fillers have poor energy efficiency, and from the perspective of green chemistry, it cannot be said that they have a high environmental load.
[0007] The present invention relates to a technology for efficiently synthesizing inorganic filler microparticles without being affected by the melting points of mother particles or daughter particles by mixing high-melting point aluminum oxide during the hetero-aggregation and melt fusion processes. The objective of the present invention is to provide a new medical / dental composition that imparts high affinity and binding power to radically polymerizable monomers, thereby imparting high mechanical strength, flexibility and durability when used in radically polymerizable cured products for medical / dental use. [Means for solving the problem]
[0008] As a result of intensive research by the inventors, it was discovered that the use of novel inorganic filler particles obtained by the following composition and manufacturing process can provide high affinity and binding power for radical polymerizable monomers, as well as flexibility. This resulted in high mechanical strength and durability when used in medical and dental materials. Item 1 The inorganic filler particles are for use in radically polymerizable cured materials for medical and dental applications, and are formed by melting and fusing a daughter particle to a mother particle. Section 2 Item 2. The inorganic filler fine particles according to item 1, wherein the mother particles have an average particle size in the range of 100 nm to 10 μm, and the daughter particles have an average particle size in the range of 1 nm to 1 μm. Section 3 3. The hetero-coagulated irregular shaped inorganic filler according to item 1 or 2, wherein both the mother particles and the daughter particles are spherical silicon dioxide. Section 4 4. The hetero-coagulated irregular shaped inorganic filler according to any one of items 1 to 3, wherein the daughter particles are obtained by a sol-gel method in which tetraethoxysilane and / or trimethoxysilane are hydrolyzed and condensed in an alkaline aqueous alcohol solvent. Section 5 A method for producing the hetero-aggregated irregular shaped inorganic filler according to any one of claims 1 to 4, comprising the steps of: 1. A process in which mother particles are surface-treated with 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane in a hydroalcoholic solvent, a suspension containing daughter particles has a pH below the isoelectric point, and when they are mixed together, hetero-aggregation occurs, causing the daughter particles to electrostatically adhere to the mother particle surfaces. 2. A process in which aluminum oxide powder and / or aluminum oxide sol is added to the mixed, dispersed, and suspended matter obtained in the previous process, and the mixed, dispersed, and suspended matter is heated and dried at a temperature not exceeding 100°C to obtain a cake. 3. The process of fusing the daughter particles to the mother particles by heating the resulting cake at a temperature in the range of 700 to 900°C. 4. A process of classifying and removing aluminum oxide using an air sieve and / or a water sieve. 5. A process of drying the hetero-aggregated irregular-shaped inorganic filler in which the daughter particles are fused to the separated mother particles. 5. A method for synthesizing a hetero-coagulated irregular shaped inorganic filler in which a daughter particle is fused to a mother particle according to any one of items 1 to 4, comprising: Section 6 Item 6. A medical and dental radically polymerizable cured material comprising the hetero-coagulated irregular shaped inorganic filler according to any one of items 1 to 5, a radically polymerizable monomer, a polymerization initiator and / or a polymerization accelerator. Effect of the Invention
[0009] By using the hetero-coagulated irregular shaped inorganic filler of the present invention, high affinity and adhesion to radical polymerizable monomers are exhibited, and as a result, dental materials are endowed with high mechanical strength, flexibility and durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The physical shape and structure of the hetero-coagulated irregular inorganic filler of the present invention is characterized in that the average particle size of the spherical mother particles is in the range of 100 nm to 10 μm, and the average particle size of the spherical daughter particles is in the range of 1 nm to 1 μm. The daughter particles are also characterized in that they are obtained by a sol-gel method in which tetraethoxysilane and / or trimethoxysilane are hydrolyzed and condensed in an alkaline aqueous alcohol solvent. The surface silanol groups of the synthesized hetero-coagulated irregular inorganic filler may be subjected to coupling treatment with a silane coupling agent having a terminal radical polymerizable group or a silane coupling agent having an epoxy ring. Furthermore, the synthesis method described below is preferable in terms of economics and environmental load. 1. A process in which mother particles are surface-treated with 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane in a hydroalcoholic solvent, a suspension containing daughter particles has a pH below the isoelectric point, and when they are mixed together, hetero-aggregation occurs, causing the daughter particles to electrostatically adhere to the mother particle surfaces. 2. A process in which aluminum oxide powder and / or aluminum oxide sol is added to the mixed, dispersed, and suspended matter obtained in the previous process, and the mixed, dispersed, and suspended matter is heated and dried at a temperature not exceeding 100°C to obtain a cake. 3. The process of fusing the daughter particles to the mother particles by heating the resulting cake at a temperature in the range of 700 to 900°C. 4. A process of classifying and removing aluminum oxide using an air sieve and / or a water sieve. 5. A process of drying the inorganic filler particles in which the daughter particles are fused to the separated mother particles. 5. A method for synthesizing inorganic filler fine particles in which daughter particles are fused to mother particles according to claim 1, comprising:
[0011] The radically polymerizable monomer used in the medical and dental radically polymerizable cured material of the present invention may be any monomer used in the dental field without any restrictions. Examples of such monomers include 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl dimethacrylate (UDMA) synthesized by the urethane reaction of 2,2,4-trimethylhexamethylene diisocyanate with 2-hydroxyethyl methacrylate (HEMA); radical polymerizable monomers synthesized by the urethane reaction of HEMA or HEA with 2,4-toluylene diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, or hexamethylene diisocyanate; urethane diacrylates obtained by the reaction of aliphatic and / or aromatic diisocyanates with glycerol (meth)acrylate or 3-methacrylol-2-hydroxypropyl ester; and urethane reactants of 1,3-bis(2-isocyanato,2-propyl)benzene with a compound having a hydroxy group. More specifically, 2,7,7,9,15-pentamethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 2,7,7,9,15-pentamethyl-4,13-18-trioxo-3,14,17-trioxa-5,12-diazaikos-19-enyl methacrylate, 2,8,10,10,15-pentamethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaikos-19-enyl methacrylate, 2,7,7,9,15-pentamethyl-4,13-dioxo-3,14-dioxa-5,1 2-Diazahexadecane-1,16-diylbis(2-methylacrylate), 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)diacrylate, 2-((2-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)cyclohexyl)methylcarbamoyloxy)propyl methacrylate, 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(bicyclo[4.1.0]heptane-3,4-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)diacrylate, 2-((4-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)bicyclo[4.1.0]heptane-3-yl)methylcarbamoyloxy)propyl methacrylate, 2,2'-(bicyclo[4.1.0]heptane-3,4-diylbis(methylene) ) Bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 7,7,9-trimethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaicos-19-enyl methacrylate, 8,10,10-trimethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaicos -19-enyl methacrylate, 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methylacrylate), 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyldiacrylate, 4,13,18-trioxo-3,14,17-trioxa-5,12-diazacos-19-enyl methacrylate, 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methyl acrylate), 2-(1-(2-((2-(acryloyloxy)ethoxy)carbonylamino)-4,4-dimethylcyclohexyl)ethylcarbamoyloxy)ethyl methacrylate, 2-(1-(2-((2-(acryloyloxy)ethoxy)carbonylamino)ethyl)-5,5-dimethylcyclohexylcarbamoyloxy)ethyl methacrylate, 2-(2-(((1-(methacryloyloxy)propan-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diylbis(2-methylacrylate), 2-(2-(((1-(methacryloyloxy)propan-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diyldiacrylate, 2-(2-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diylbis(2-methylacrylate), 3-(15-(2-(acryloyloxy)ethyl)-3,12,1 9-trioxo-2,13,18-trioxa-4,11-diazahenicos-20-enyl)pentane-1,5-diyl diacrylate, 3-(15-(2-(acryloyloxy)ethyl)-3,12,19-trioxo-2,13,18-trioxa-4,11-diazahenicos-20-enyl)pentane-1,5-diyl bis(2-methylacrylate), 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-((2 -(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)cyclohexyl)methylcarbamoyloxy)ethyl methacrylate, 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methylacrylate), 2,15-bis(cyclohexyloxymethyl)-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 2,15-bis(cyclohexyloxymethyl)-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 1,18-bis(cyclohexyloxy)-5,14-dioxo-4,15-dioxa-6,13-diazaoctadecane-2,17-diyl diacrylate, 1-(cyclohexyloxy)-17-(cyclohexyloxymethyl)-5,14,19-trioxo-4,15,18-trioxa-6,13-diazahenicos-20-en-2-yl methacrylate, 1,18-bis(cyclohexyloxy)-5,14-dioxo-4,15-dioxa-6,13-diazaoctadecane-2,17-diylbis(2-methylacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methylacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5, 12-Diazahexadecane-1,16-diyl diacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-(3-(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)benzylcarbamoyloxy)ethyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-((3-((((2-(acryloyloxy)ethoxy)carbonyl)(methyl)amino)methyl)benzyl)(methyl)carbamoyloxy)ethyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl) diacrylate, 2-(3-(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)benzylcarbamoyloxy)propyl methacrylate, 2-(3-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)ethyl Methacrylate, 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bisoxomethylene)bis(oxy)bis(4,1-phenylene)bis(2-methylacrylate), 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bisoxomethylene)bis(oxy)bis(4,1-phenylene)diacrylate, 4-(3-(((4-(acryloxy)phenoxy)carbonylamino)methyl)benzylcarbamoyloxy)phenyl Methacrylate, 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)bis(2-methylacrylate), 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)diacrylate, 4-(3-(((4-(acryloyloxy)butoxy)carbonylamino)methyl)benzylcarbamoyloxy)butyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-phenoxypropan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-phenoxypropyl Methacrylate, 2-2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)bis(2-methylacrylate), 2-2'-(1,3-Phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-(phenylamino)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(phenylamino)propyl methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene) )bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloxy)-3-(phenylthio)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(phenylthio)propyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(benzyloxy)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(benzyloxy)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-(benzyloxy)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(benzyloxy)propyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(methacryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(acryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-(2-phenylacetoxy)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(2-phenylacetoxy)propyl Methacrylate 2,2'-(2,2'-(1,3-phenylene)bis(propane-2.2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2.2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-(2-(3-(2-((2-(acryloyloxy)ethoxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)ethyl methacrylate, 2 ,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-((2-(3-(2-(((2-(acryloyloxy)ethoxy)carbonyl)(methyl)amino)propan-2-yl)phenyl)propan-2-yl)(methyl)carbamoyloxy)ethyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl) diacrylate, 2-(2-(3-(2-((2-(acryloyloxy)ethoxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)propyl methacrylate, 2-(2-(3-(2-((1-(acryloyloxy)propan-2-yloxy)carbonylamino)propan-2-ylcarbamoyloxy)ethyl Methacrylate, 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(4,1-phenylene)bis(2-methylacrylate), 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(4,1-phenylene ) diacrylate, 4-(2-(3-(2-((4-(acryloyloxy)phenoxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)phenyl methacrylate, 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)bis(2-meth acrylate), 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)diacrylate, 4-(2-(3-(2-((4-acryloyloxy)butoxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)butyl methacrylate, 2,2' -(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)bis(2-methacrylate); 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl) diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-phenoxypropan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-phenoxypropyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(phenylamino)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(phenylamino)propyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(phenylthio)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(phenylthio)propyl Methacrylate, 2-2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(3-(benzyloxy)propane-2,1-diyl)bis(2-methylacrylate), 2-2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(3-(benzyloxy)propane-2,1-diyl) diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(benzyloxy)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(benzyloxy)propyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(methacryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(acryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene) )bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(2-phenylacetoxy)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(2-phenylacetoxy)propyl methacrylate, etc.
[0012] The polymerization initiator contained in the medical and dental radical polymerizable cured product of the present invention can be selected from polymerization initiators used in the industrial field, and among them, polymerization initiators used for dental applications are preferably used. In particular, photopolymerization and chemical polymerization initiators are used alone or in appropriate combination of two or more. Specifically, photopolymerization initiators among the polymerization initiators contained in the medical and dental radical polymerizable cured product of the present invention include (bis)acylphosphine oxides, water-soluble acylphosphine oxides, thioxanthones or quaternary ammonium salts of thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, α-aminoketone compounds, etc. The ratio of these to the radical polymerizable monomer is preferably 0.5wt% to 5wt%. At a concentration lower than 0.5wt%, the amount of unpolymerized radical polymerizable monomer increases, resulting in a decrease in mechanical strength. At a concentration higher than 5wt%, the degree of polymerization decreases, resulting in a decrease in mechanical strength.
[0013] Specific examples of acylphosphine oxides used as photopolymerization initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, and benzoyldi-(2,6-dimethylphenyl)phosphonate. Examples of the bisacylphosphine oxides include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and (2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.
[0014] Specific examples of thioxanthones or quaternary ammonium salts of thioxanthones used as photopolymerization initiators include thioxanthones, 2-chlorothioxanthen-9-one, 2-hydroxy-3-(9-oxy-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-propanaminium chloride, 2-hydroxy-3-(1-methyl-9-oxy-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-propanaminium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N ,N,N-trimethyl-propanaminium chloride, 2-hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(3,4-dimethyl-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1,3,4-trimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, and the like.
[0015] Specific examples of α-diketones used as photopolymerization initiators include diacetyl, dibenzyl, camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4'-oxybenzyl, and acenaphthenequinone.
[0016] Specific examples of coumarin compounds used as photopolymerization initiators include 3,3'-carbonylbis(7-diethylamino)coumarin, 3-(4-methoxybenzoyl)coumarin, 3-thenoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, yl)coumarin, 3-benzoyl-8-methoxycoumarin, 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromocoumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 7-meth 3-(4-nitrobenzoyl)coumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3-(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzyl)coumarin, 3-(4-phenyl-1,2-diphenylamino)-1,2-diphenyl-2,3-diphenyl ...3'-carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazoyl)-7-(diethylamino)coumarin, 3-(2-benzothiazoyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazoyl)-7-(diethylamino)coumarin, 3-(2-benzothiazoyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylaminocoumarin), 3,3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-1,1,7,7-tetramethyl1H,5H,11H-[1]benzopyrano, [6,7,8-ij]quinolizin-11-one, 10-(2-benzothiazoyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, and the like.
[0017] Among the coumarin compounds, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly preferred.
[0018] Specific examples of anthraquinones used as photopolymerization initiators include anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1-bromoanthraquinone, 1,2-benzanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, and 1-hydroxyanthraquinone.
[0019] Specific examples of benzoin alkyl ethers used as photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0020] Specific examples of α-aminoketones used as photopolymerization initiators include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one.
[0021] Among the photopolymerization initiators, it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides and their salts, α-diketones, and coumarin compounds, which provides a composition that is excellent in photocurability in the visible and near-ultraviolet regions and exhibits sufficient photocurability when using any of the light sources, such as a halogen lamp, a light-emitting diode (LED), and a xenon lamp.
[0022] Of the polymerization initiators contained in the medical and dental radically polymerizable cured material of the present invention, organic peroxides are preferably used as the chemical polymerization initiator. The organic peroxides used as the above-mentioned chemical polymerization initiators are not particularly limited, and known ones can be used. Representative organic peroxides include ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates.
[0023] Specific examples of the ketone peroxide used as the chemical polymerization initiator include methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, methylcyclohexanone peroxide, and cyclohexanone peroxide.
[0024] Specific examples of hydroperoxides used as chemical polymerization initiators include 2,5-dimethylhexane-2,5-dihydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.
[0025] Specific examples of diacyl peroxides used as chemical polymerization initiators include acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, decanoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide.
[0026] Specific examples of dialkyl peroxides used as chemical polymerization initiators include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne.
[0027] Specific examples of peroxyketals used as chemical polymerization initiators include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, and 4,4-bis(t-butylperoxy)valeric acid-n-butyl ester.
[0028] Specific examples of peroxy esters used as chemical polymerization initiators include α-cumyl peroxy neodecanoate, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, 2,2,4-trimethylpentyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, di-t-butyl peroxy isophthalate, di-t-butyl peroxy hexahydroterephthalate, t-butyl peroxy-3,3,5-trimethylhexanoate, t-butyl peroxy acetate, t-butyl peroxy benzoate, and t-butyl peroxy maleric acid.
[0029] Specific examples of peroxydicarbonates used as chemical polymerization initiators include di-3-methoxyperoxydicarbonate, di-2-ethylhexylperoxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, diisopropylperoxydicarbonate, di-n-propylperoxydicarbonate, di-2-ethoxyethylperoxydicarbonate, and diallylperoxydicarbonate.
[0030] Among the organic peroxides, diacyl peroxides are preferably used from the viewpoint of the overall balance of safety, storage stability, and radical generating ability, and among them, benzoyl peroxide is particularly preferably used.
[0031] Specific examples of the polymerization accelerator include amines, sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, and thiol compounds.
[0032] The amines used as polymerization accelerators are divided into aliphatic amines and aromatic amines. Specific examples of aliphatic amines include primary aliphatic amines such as n-butylamine, n-hexylamine, and n-octylamine; secondary aliphatic amines such as diisopropylamine, dibutylamine, and N-methyldiethanolamine; and tertiary aliphatic amines such as N-methylethanolamine, N-ethyldiethanolamine, N-n-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among these, tertiary aliphatic amines are preferred from the viewpoint of the curability and storage stability of the composition, and N-methyldiethanolamine and triethanolamine are more preferably used.
[0033] Specific examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-di(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-diisopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, and N,N-dimethyl-m-toluidine. 4-N,N-dimethylaminobenzoic acid ethyl ester, 4-N,N-dimethylaminobenzoic acid methyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, 4-N,N-dimethylaminobenzoic acid-2-(methacryloyloxy)ethyl ester, 4-N,N-dimethylaminobenzophenone, and 4-dimethylaminobenzoic acid butyl ester. Among these, from the viewpoint of imparting excellent curing properties to the composition, N,N-di(2-hydroxyethyl)-p-toluidine, 4-N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, and 4-N,N-dimethylaminobenzophenone can be mentioned.
[0034] Specific examples of sulfinic acid and its salts used as the polymerization accelerator include p-toluenesulfinic acid, sodium p-toluenesulfinate, potassium p-toluenesulfinate, lithium p-toluenesulfinate, calcium p-toluenesulfinate, benzenesulfinic acid, sodium benzenesulfinate, potassium benzenesulfinate, lithium benzenesulfinate, calcium benzenesulfinate, 2,4,6-trimethylbenzenesulfinic acid, sodium 2,4,6-trimethylbenzenesulfinate, potassium 2,4,6-trimethylbenzenesulfinate, lithium 2,4,6-trimethylbenzenesulfinate, calcium 2,4,6-trimethylbenzenesulfinate, 2,4,6-triethylbenzenesulfinate, and 2,4,6-triethylbenzenesulfinate. Examples of the sulfinic acid include benzenesulfinic acid, sodium 2,4,6-triethylbenzenesulfinate, potassium 2,4,6-triethylbenzenesulfinate, lithium 2,4,6-triethylbenzenesulfinate, calcium 2,4,6-triethylbenzenesulfinate, 2,4,6-triisopropylbenzenesulfinic acid, sodium 2,4,6-triisopropylbenzenesulfinate, potassium 2,4,6-triisopropylbenzenesulfinate, lithium 2,4,6-triisopropylbenzenesulfinate, and calcium 2,4,6-triisopropylbenzenesulfinate. Of these, sodium benzenesulfinate, sodium p-toluenesulfinate, and sodium 2,4,6-triisopropylbenzenesulfinate are particularly preferred.
[0035] Specific examples of the borate compound used as the polymerization accelerator include borate compounds having one aryl group per molecule, such as trialkylphenyl boron, trialkyl(p-chlorophenyl) boron, trialkyl(p-fluorophenyl) boron, trialkyl(3,5-bistrifluoromethyl) phenyl boron, trialkyl[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl) phenyl] boron, trialkyl(p-nitrophenyl) boron, trialkyl(m-nitrophenyl) boron, trialkyl(p-butylphenyl) boron, trialkyl(m-butylphenyl) boron, and trialkyl(p-butylphenyl) boron. Examples of the alkyl group include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of trialkyl(p-butyloxyphenyl)boron, trialkyl(m-butyloxyphenyl)boron, trialkyl(p-octyloxyphenyl)boron, and trialkyl(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).
[0036] Specific examples of borate compounds having two aryl groups in one molecule include dialkyldiphenylboron, dialkyldi(p-chlorophenyl)boron, dialkyldi(p-fluorophenyl)boron, dialkyldi(3,5-bistrifluoromethyl)phenylboron, dialkyldi[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, dialkyldi(p-nitrophenyl)boron, dialkyldi(m-nitrophenyl)boron, dialkyldi(p-butylphenyl)boron, dialkyldi(m-butylphenyl)boron, and dialkyldi(p-butyloxophenyl)boron. Examples of such salts include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of dialkyldi(m-butyloxyphenyl)boron, dialkyldi(p-octyloxyphenyl)boron, and dialkyldi(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).
[0037] Further, specific examples of borate compounds having three aryl groups in one molecule include monoalkyltriphenylboron, monoalkyltri(p-chlorophenyl)boron, monoalkyltri(p-fluorophenyl)boron, monoalkyltri(3,5-bistrifluoromethyl)phenylboron, monoalkyltri[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, monoalkyltri(p-nitrophenyl)boron, monoalkyltri(m-nitrophenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(m-butyl ... Examples of the alkyl group include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of alkyltri(p-butyloxyphenyl)boron, monoalkyltri(m-butyloxyphenyl)boron, monoalkyltri(p-octyloxyphenyl)boron, and monoalkyltri(m-octyloxyphenyl)boron (wherein the alkyl group is one selected from an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).
[0038] Further specific examples of borate compounds having four aryl groups in one molecule include tetraphenylboron, tetrakis(p-chlorophenyl)boron, tetrakis(p-fluorophenyl)boron, tetrakis(3,5-bistrifluoromethyl)phenylboron, tetrakis[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, tetrakis(p-nitrophenyl)boron, tetrakis(m-nitrophenyl)boron, tetrakis(p-butylphenyl)boron, tetrakis(m-butylphenyl)boron, tetrakis(p-butyloxyphenyl)boron, tetrakis(m-butyloxyphenyl)boron, tetrakis(p-octyloxyphenyl)boron, Examples of the salt include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of (m-octyloxyphenyl)boron, (p-fluorophenyl)triphenylboron, (3,5-bistrifluoromethyl)phenyltriphenylboron, (p-nitrophenyl)triphenylboron, (m-butyloxyphenyl)triphenylboron, (p-butyloxyphenyl)triphenylboron, (m-octyloxyphenyl)triphenylboron, and (p-octyloxyphenyl)triphenylboron.
[0039] Among these aryl borate compounds, it is more preferable to use a borate compound having 3 or 4 aryl groups in one molecule from the viewpoint of storage stability. In addition, these aryl borate compounds can be used alone or in combination of two or more kinds.
[0040] Specific examples of barbituric acid derivatives used as polymerization accelerators include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethylbarbituric acid, 1,3-dimethyl-5-cyclopentylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-1-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 5-methylbarbituric acid, Examples of barbituric acids include 1-cyclohexyl-5-methylbarbituric acid, 1-ethyl-5-isobutylbarbituric acid, 1,3-diethyl-5-butylbarbituric acid, 1-cyclohexyl-5-methylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-cyclohexyl-5-octylbarbituric acid, 1-cyclohexyl-5-hexylbarbituric acid, 5-butyl-1-cyclohexylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and thiobarbituric acids, as well as salts thereof (particularly preferred are those of alkali metals or alkaline earth metals). Examples of the salts of barbituric acids include sodium 5-butylbarbiturate, sodium 1,3,5-trimethylbarbiturate, and sodium 1-cyclohexyl-5-ethylbarbiturate.
[0041] Specific examples of particularly suitable barbituric acid derivatives include 5-butylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and sodium salts of these barbituric acids.
[0042] Specific examples of triazine compounds used as polymerization accelerators include 2,4,6-tris(trichloromethyl)-s-triazine, 2,4,6-tris(tribromomethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(tribromomethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methylthiophene)-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methylthiophene)-4,6-bis(trichloromethyl)-s-triazine. phenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2,4-dichlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-bromophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-n-propyl-4,6-bis(trichloromethyl)-s-triazine, 2-(α,α,β-trichloroethyl) -4,6-bis(trichloromethyl)-s-triazine, 2-styryl-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(o-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-butoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4-dimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, chloromethyl)-s-triazine, 2-[2-(3,4,5-trimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-(1-naphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N,N-bis(2-hydroxyethyl)amino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-ethylamino}ethoxy]-4,Examples include 6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-methylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, and 2-[2-{N,N-diallylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine.
[0043] Among the above-listed triazine compounds, 2,4,6-tris(trichloromethyl)-s-triazine is particularly preferred in terms of polymerization activity, and 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine are particularly preferred in terms of storage stability. The above-listed triazine compounds may be used alone or in combination of two or more.
[0044] Specific examples of copper compounds used as polymerization accelerators include copper acetylacetonate, copper acetate, copper oleate, copper chloride, and copper bromide.
[0045] Specific examples of tin compounds used as polymerization accelerators include di-n-butyltin dimaleate, di-n-octyltin dimaleate, di-n-octyltin dilaurate, di-n-butyltin dilaurate, etc. Particularly preferred tin compounds are di-n-octyltin dilaurate and di-n-butyltin dilaurate.
[0046] The vanadium compound used as the polymerization accelerator is preferably a tetravalent and / or pentavalent vanadium compound. Specific examples of the tetravalent and / or pentavalent vanadium compound include divanadium tetroxide (tetravalent), vanadium oxide acetylacetonate (tetravalent), vanadyl oxalate (tetravalent), vanadyl sulfate (tetravalent), oxo-bis(1-phenyl-1,3-butanedionato)vanadium (tetravalent), bis(maltolato)oxo-vanadium (tetravalent), vanadium pentoxide (pentavalent), sodium metavanadate (pentavalent), and ammonium metavanadate (pentavalent).
[0047] Specific examples of halogen compounds used as polymerization accelerators include dilauryl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, benzyl trimethyl ammonium chloride, tetramethyl ammonium chloride, benzyl dimethyl cetyl ammonium chloride, and dilauryl dimethyl ammonium bromide.
[0048] Specific examples of aldehydes used as polymerization accelerators include terephthalaldehyde and benzaldehyde derivatives. Examples of benzaldehyde derivatives include dimethylaminobenzaldehyde, p-methyloxybenzaldehyde, p-ethyloxybenzaldehyde, and p-n-octyloxybenzaldehyde. Among these, p-n-octyloxybenzaldehyde is preferably used from the viewpoint of curability.
[0049] Specific examples of the thiol compound used as the polymerization accelerator include 3-mercaptopropyltrimethoxysilane, 2-mercaptobenzoxazole, decanethiol, and thiobenzoic acid. EXAMPLES
[0050] The method for producing the polymer surfactant according to the present invention and the preparation method and physical properties of the dental hardenable composition containing the same will be described in detail below, but the present invention is not limited to these descriptions in any way. Synthesis Example 1 A hetero-aggregated irregular inorganic filler was synthesized with the compounding composition shown in Table 1. That is, 50.0 g of spherical silicon dioxide (HPS-2000, manufactured by Toa Gosei Co., Ltd.) and 1.0 L of distilled water were weighed in a 2 L eggplant flask equipped with an electromagnetic stirrer, and thoroughly dispersed with an ultrasonic generator (GSD150AT manufactured by Sonic Technology Co., Ltd.). Then, the internal temperature was raised to 75°C in an oil bath while stirring, and 1.50 g of 3-aminopropyl triethoxysilane was added at a rate of 10 mL / h. After the addition was completed, the mixture was aged at 75°C for 2 hours. After separation by centrifugation, the mixture was dispersed in 0.50 L of EtOH to obtain mother particles. Next, 375 g of TEOS and 1.0 L of EtOH were weighed in a 3 L eggplant flask equipped with an electromagnetic stirrer, and thoroughly stirred and mixed. To the mixed solution, a solution of 2.0g NaOH / 0.50L distilled water was added at a rate of 500mL / h under stirring, and the mixture was aged for 2 hours. Next, 1N-HCl was added little by little until the pH reached 3. The mother particle suspension prepared above was then added and thoroughly stirred. The suspension of the obtained mother particles and daughter particles in hetero-aggregation was concentrated in an evaporator until the solvent was reduced to almost half. To the concentrate, 50g of alumina powder with an average particle size of 10nm and 1L of ethanol dispersion suspension were added and mixed. The mixed suspension was transferred to a zirconia drying dish and dried at 50℃ for 6 hours. The obtained cake-like solid was fired in air at 900℃ for 2 hours. After firing, it was cooled to room temperature. The cake-like solid was strong enough to be easily crumbled by finger pressure. The cake was separated from the alumina powder using a sieve to obtain a hetero-aggregated irregular shaped inorganic filler. Scanning electron microscope images of the hetero-aggregated irregular shaped inorganic filler are shown in Figures 1 and 2. Synthesis Example 2 A hetero-aggregated irregular inorganic filler was synthesized with the compounding composition shown in Table 1. That is, 50.0 g of spherical silicon dioxide (HPS-2000, manufactured by Toa Gosei Co., Ltd.) and 1.0 L of distilled water were weighed in a 2 L eggplant flask equipped with an electromagnetic stirrer, and thoroughly dispersed with an ultrasonic generator (GSD150AT manufactured by Sonic Technology Co., Ltd.). Then, the internal temperature was raised to 75°C in an oil bath while stirring, and 1.50 g of 3-aminopropyl triethoxysilane was added at a rate of 10 mL / h. After the addition was completed, the mixture was aged at 75°C for 2 hours. After separation by centrifugation, the mixture was dispersed in 0.50 L of EtOH to obtain mother particles. Next, 375 g of TEOS and 1.0 L of EtOH were weighed in a 3 L eggplant flask equipped with an electromagnetic stirrer, and thoroughly stirred and mixed. To the mixed solution, a solution of 2.0g NaOH / 0.50L distilled water was added at a rate of 400mL / h under stirring, and the mixture was aged for 2 hours. Next, 1N-HCl was added little by little until the pH reached 3. The previously prepared mother particle suspension was then added and thoroughly stirred. The suspension of the obtained mother particles and daughter particles in hetero-aggregation was concentrated in an evaporator until the solvent was reduced to almost half. To the concentrate, 50g of alumina powder with an average particle size of 10nm and 1L of ethanol dispersion suspension were added and mixed. The mixed suspension was transferred to a zirconia drying dish and dried at 50℃ for 6 hours. The obtained cake-like solid was fired in air at 900℃ for 2 hours. After firing, it was cooled to room temperature. The cake-like solid was strong enough to be easily crumbled by finger pressure. The cake was separated from the alumina powder using a sieve to obtain a hetero-aggregated irregular shaped inorganic filler. Synthesis Example 3 A hetero-aggregated irregular inorganic filler was synthesized with the compounding composition shown in Table 1. That is, 50.0 g of spherical silicon dioxide (HPS-2000, manufactured by Toa Gosei Co., Ltd.) and 1.0 L of distilled water were weighed in a 2 L eggplant flask equipped with an electromagnetic stirrer, and thoroughly dispersed with an ultrasonic generator (GSD150AT manufactured by Sonic Technology Co., Ltd.). Then, the internal temperature was raised to 75°C in an oil bath while stirring, and 1.50 g of 3-aminopropyl triethoxysilane was added at a rate of 10 mL / h. After the addition was completed, the mixture was aged at 75°C for 2 hours. After separation by centrifugation, the mixture was dispersed in 0.50 L of EtOH to obtain mother particles. Next, 375 g of TEOS and 1.0 L of EtOH were weighed in a 3 L eggplant flask equipped with an electromagnetic stirrer, and thoroughly stirred and mixed. To the mixed solution, a solution of 2.0g NaOH / 0.50L distilled water was added at a rate of 300mL / h under stirring, and the mixture was aged for 2 hours. Next, 1N-HCl was added little by little until the pH reached 3. The previously prepared mother particle suspension was then added and thoroughly stirred. The suspension of the obtained mother particles and daughter particles in hetero-aggregation was concentrated in an evaporator until the amount of solvent was almost half. To the concentrate, 50g of alumina powder with an average particle size of 10nm and 1L of ethanol dispersion suspension were added and mixed. The mixed suspension was transferred to a zirconia drying dish and dried at 50℃ for 6 hours. The obtained cake-like solid was fired in air at 900℃ for 2 hours. After firing, it was cooled to room temperature. The cake-like solid was strong enough to be easily crumbled by finger pressure. The cake was separated into alumina powder using a sieve, and a hetero-aggregated irregular shaped inorganic filler was obtained. Synthesis Example 4 Hetero-aggregated irregular inorganic filler was synthesized with the compounding composition shown in Table 1. That is, 50.0g of spherical silicon dioxide (HPS-2000, manufactured by Toa Gosei Co., Ltd.) and 1.0L of distilled water were weighed in a 2L eggplant flask equipped with an electromagnetic stirrer, and thoroughly dispersed with an ultrasonic generator (GSD150AT manufactured by Sonic Technology Co., Ltd.). Then, the internal temperature was raised to 75°C in an oil bath while stirring, and 1.50g of 3-aminopropyl triethoxysilane was added at a rate of 10mL / h. After the addition was completed, the mixture was aged at 75°C for 2 hours. After separation by centrifugation, the mixture was dispersed in 0.50L of EtOH to obtain mother particles. Next, 300g of TEOS and 1.0L of EtOH were weighed in a 3L eggplant flask equipped with an electromagnetic stirrer, and thoroughly stirred and mixed. To the mixed solution, a solution of 2.0g NaOH / 0.50L distilled water was added at a rate of 500mL / h under stirring, and the mixture was aged for 2 hours. Next, 1N-HCl was added little by little until the pH reached 3. The previously prepared mother particle suspension was then added and thoroughly stirred. The suspension of the obtained mother particles and daughter particles in hetero-aggregation was concentrated in an evaporator until the amount of solvent was almost half. To the concentrate, 50g of alumina powder with an average particle size of 10nm and 1L of ethanol dispersion suspension were added and mixed. The mixed suspension was transferred to a zirconia drying dish and dried at 50℃ for 6 hours. The obtained cake-like solid was fired in air at 900℃ for 2 hours. After firing, it was cooled to room temperature. The cake-like solid was strong enough to be easily crumbled by finger pressure. The cake was separated into alumina powder using a sieve to obtain a hetero-aggregated irregular shaped inorganic filler. Synthesis Example 5 Hetero-aggregated irregular inorganic filler was synthesized with the compounding composition shown in Table 1. That is, 50.0g of spherical silicon dioxide (HPS-2000, manufactured by Toa Gosei Co., Ltd.) and 1.0L of distilled water were weighed in a 2L eggplant flask equipped with an electromagnetic stirrer, and thoroughly dispersed with an ultrasonic generator (GSD150AT manufactured by Sonic Technology Co., Ltd.). Then, the internal temperature was raised to 75°C in an oil bath while stirring, and 1.50g of 3-aminopropyl triethoxysilane was added at a rate of 10mL / h. After the addition was completed, the mixture was aged at 75°C for 2 hours. After separation by centrifugation, the mixture was dispersed in 0.50L of EtOH to obtain mother particles. Next, 450g of TEOS and 1.0L of EtOH were weighed in a 3L eggplant flask equipped with an electromagnetic stirrer, and thoroughly stirred and mixed. To the mixed solution, a solution of 2.0g NaOH / 0.50L distilled water was added at a rate of 500mL / h under stirring, and the mixture was aged for 2 hours. Next, 1N-HCl was added little by little until the pH reached 3. The previously prepared mother particle suspension was then added and thoroughly stirred. The suspension of the obtained mother particles and daughter particles in hetero-aggregation was concentrated in an evaporator until the amount of solvent was almost half. To the concentrate, 50g of alumina powder with an average particle size of 10nm and 1L of ethanol dispersion suspension were added and mixed. The mixed suspension was transferred to a zirconia drying dish and dried at 50℃ for 6 hours. The obtained cake-like solid was fired in air at 900℃ for 2 hours. After firing, it was cooled to room temperature. The cake-like solid was strong enough to be easily crumbled by finger pressure. The cake was separated into alumina powder using a sieve to obtain a hetero-aggregated irregular shaped inorganic filler.
[0051] Examples 1-5 The hetero-aggregated irregular inorganic fillers synthesized in Synthesis Examples 1 to 5 and OX-50 (manufactured by Nippon Aerosil Co., Ltd.) were used. MedicalDental composite resin was prepared. The specific manufacturing method is described in detail below. The amount of hetero-aggregated irregular inorganic filler and OX-50 shown in Table 2 were added to a 500 mL eggplant flask. Then, 200 mL of acetone was added, and an electromagnetic stirrer was added and stirred for 10 minutes, and the mixture was dispersed for 5 minutes using an ultrasonic disperser at 28 KHz and 150 W. After dispersion, the binder liquid (UDMA, 2G) and photopolymerization initiator shown in Table 2 were added and thoroughly stirred, and then the acetone was removed using an evaporator. Next, the mixture was degassed and kneaded under conditions of 1000 rpm, 5 KPa, and 15 min in a Thinky Planetary Vacuum Mixer ARV-310 in the dark to obtain a dental composite resin. The medical and dental composite resin obtained in this way was hardened according to ISO4049, and bending strength was measured using an Instron universal testing machine (Instron 5567, Instron). The photopolymerization irradiator used was Griplight II manufactured by Shofu Co., Ltd. Comparative Examples 1-5 Using HPS2000 and OX-50 (manufactured by Nippon Aerosil Co., Ltd.) Medical Dental composite resin was prepared. The specific manufacturing method is described in detail below. The amounts of HPS2000 and OX-50 shown in Table 3 were added to a 500 mL eggplant flask. Then, 200 mL of acetone was added, and the mixture was stirred for 10 minutes with an electromagnetic stirrer, and dispersed for 5 minutes with a 28 KHz-150 W ultrasonic disperser. After dispersion, the binder liquid (UDMA, 2G) and photopolymerization initiator shown in Table 3 were added and thoroughly stirred, and then the acetone was removed with an evaporator. Next, the mixture was degassed and kneaded under conditions of 1000 rpm-5 KPa-15 min in a Thinky Planetary Vacuum Mixer ARV-310 in the dark to obtain a dental composite resin. The medical and dental composite resin obtained in this way was hardened according to ISO4049, and bending strength was measured using an Instron universal testing machine (Instron 5567, Instron). The photopolymerization irradiator used was Griplight II manufactured by Shofu Co., Ltd.
[0052] The bending strength test results of the dental composite resins prepared in the Examples and Comparative Synthesis Examples are shown in Tables 4 and 5. As is clear from these results, the dental composite resins containing the hetero-aggregated irregular inorganic filler of the present invention have clearly higher bending strength properties than the medical and dental composite resins synthesized in the Comparative Synthesis Examples. It is scientifically believed that this experimental fact is due to the cohesive force of the filler. That is, as can be seen from Figures 1 and 2, it is believed that the resin (monomer hardened body) that entered the unevenness of the inorganic filler affected the bending strength. As a result, the dental material was given high mechanical strength and durability. As a result, it became possible to achieve high mechanical strength. As is clear from the above evaluation results, it became possible to provide medical and dental materials with high mechanical strength and flexibility that could not be achieved by conventional technology.
[0053] [Table 1]
[0054] [Table 2]
[0055] [Table 3]
[0056] [Table 4]
[0057] [Table 5]
[0058] TIFF0007626985000006.tif128158
[0059] TIFF0007626985000007.tif126159Possible industrial applications
[0060] In medical and dental composite resins, (meth)acrylic acid derivative monomers such as methyl methacrylate, triethylene glycol dimethacrylate, and urethane dimethacrylate are used. In the free radical polymerization (hereinafter referred to as radical polymerization) of vinyl monomers such as these (meth)acrylic acid derivative monomers, the carbon-carbon double bonds are cleaved to single bonds to form a polymer and harden. In addition to vinyl monomers, inorganic fillers are added to this composite resin for the purpose of improving mechanical strength. Generally, these inorganic fillers are spherical or crushed. These inorganic fillers have low cohesive power and are limited in terms of obtaining high physical strength. In addition, the conventional manufacturing method for irregularly shaped inorganic fillers has limitations on the melting points of the mother particles and daughter particles. Furthermore, the synthesis of these materials requires many steps and is inefficient. In other words, the environmental load is high. The medical and dental materials containing the hetero-aggregated irregularly shaped inorganic filler according to the present invention have flexibility and high physical properties, so they overcome all of these problems and have great potential for industrial use.
Claims
[Claim 1] A method for producing inorganic filled fine particles in which a daughter particle is fused to a mother particle, comprising the steps of: A step of surface-treating the mother particles with 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane in a water-containing alcohol solvent; a step of mixing a suspension containing daughter particles having a pH equal to or lower than the isoelectric point with a suspension containing mother particles to obtain hetero-aggregates; mixing aluminum oxide powder and / or aluminum oxide sol with the suspension containing the hetero-aggregates to obtain an aluminum oxide-containing suspension; a step of heating and drying the aluminum oxide-containing suspension at 100° C. or less; heating the heat-dried aluminum oxide-containing suspension at a temperature in the range of 700° C. to 900° C.; A step of classifying and removing the aluminum oxide using an air sieve and / or a water sieve; A method for producing inorganic filling particles comprising the steps of:
Citation Information
Patent Citations
Production of formed silicon nitride
JP1989052677A
Dental reparative material
JP1990134307A
Surface treatment of inorganic filler
JP1991070778A
Inorganic filler tending to remain and its production
JP1995173410A
Silane coupling agent, and composite resin for dental application and primer for dental application each comprising the silane coupling agent
JP2007238567A